High crack resistance and low hydration heat crack sensitive engineering cement concrete

CN122916563APending Publication Date: 2026-10-16DAZHOU MAOYUAN BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610586888.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,这一大掺量技术路线在实践中引发了新的突出矛盾:大量惰性或低活性掺合料的引入,虽然有效降低了温升,但严重延缓了水泥的水化进程,导致混凝土早期强度发展显著迟缓、凝结时间延长

Benefits of technology

[0028] The technical effects and advantages of this invention are as follows: By combining sulfoaluminate cement with ultrafine composite admixtures in a specific ratio and employing a three-step premixing process, various properties of concrete are coordinated as a whole. The significant microcrystalline nucleation effect of limestone powder at low dosage effectively promotes early hydration and specifically enhances the early strength of concrete; simultaneously, its micro-aggregate filling effect further optimizes the slurry structure, enhancing density and volume stability. The synergistic effect of these two factors achieves precise control over the hydration process and microstructure. This solution not only utilizes the advantages of sulfoaluminate cement and ultrafine composite admixtures to effectively control hydration heat release, but more importantly, its unique three-step premixing process solves the practical mixing problems of uneven dispersion and poor workability of such ultrafine powders and fibers at low water-cement ratios, thus ensuring the density and early strength development of the concrete structure. The resulting concrete, while meeting the requirements of extremely low heat of hydration in crack-sensitive engineering, still exhibits good early crack resistance and workability, achieving simultaneous optimization of multiple key properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916563A_ABST
    Figure CN122916563A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high crack resistance low hydration heat's crack sensitive engineering cement concrete, including the following components by weight parts: sulphoaluminate cement 280-350 parts;Composite admixture 90-150 parts, the composite admixture includes superfine fly ash, silica fume and zeolite powder;Basalt fiber 0.8-4.5 parts;Water reducing agent 4.5-7.0 parts;Viscosity regulator 0.1-0.4 parts;Water 130-160 parts.The cement concrete also includes limestone powder.The application also discloses a kind of preparation high crack resistance low hydration heat's crack sensitive engineering cement concrete described above method.The application realizes low heat by sulphoaluminate cement and superfine admixture cooperation, low water glue ratio and fiber guarantee early strength crack resistance, mixed limestone powder uses its microcrystalline nuclear effect to promote early strength, and by micro aggregate filling optimization density and stability, so that concrete meets the comprehensive requirement of low heat, high early strength and high crack resistance for crack sensitive engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and more specifically, to a type of crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration. Background Technology

[0002] Concrete is the most important structural material in various construction projects. In "crack-sensitive projects" such as large foundations, hydraulic structures, and super-long bridges, where crack control requirements are extremely high, concrete must not only meet the design strength, but also have extremely low heat of hydration to avoid temperature cracks, and high early crack resistance to resist shrinkage stress.

[0003] Currently, the most common and effective technical approach to reducing the heat of hydration in concrete is to significantly increase the amount of mineral admixtures such as fly ash and mineral powder, replacing a portion of the cement. However, this high-admixture approach has led to new and prominent contradictions in practice: while the introduction of large amounts of inert or low-activity admixtures effectively reduces temperature rise, it severely delays the cement hydration process, resulting in significantly slower early strength development and prolonged setting time in concrete. Simultaneously, some admixtures may increase the drying shrinkage of the system. This results in low strength and easy shrinkage of concrete in the critical early stages after pouring, weakening its crack resistance and failing to meet the rapid construction pace and stringent requirements for high early crack resistance in modern engineering projects. Furthermore, fiber materials added to improve toughness are more prone to uneven dispersion in high-admixture systems, exacerbating the difficulty of construction quality control.

[0004] Therefore, the current state of technology shows that simply increasing the amount of mineral admixtures to reduce the heat of hydration is incompatible with the core requirements of rapid construction, early strength and early crack resistance necessary for crack-sensitive projects, and there is an urgent need for a new type of cement concrete. Summary of the Invention

[0005] In order to overcome the above-mentioned defects of the prior art, the present invention provides a crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration, and solves the problems mentioned in the background art through the following solutions.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration, comprising the following components by weight:

[0007] 280-350 parts of sulfoaluminate cement;

[0008] 90-150 parts of composite admixture, wherein the composite admixture comprises ultrafine fly ash, silica fume and zeolite powder;

[0009] Basalt fiber 0.8-4.5 parts;

[0010] Water-reducing agent: 4.5-7.0 parts;

[0011] Viscosity modifier 0.1-0.4 parts;

[0012] 130-160 parts water;

[0013] The water-cement ratio of the cement concrete is 0.34-0.39.

[0014] Preferably, in the composite admixture, the weight ratio of ultrafine fly ash, silica fume and zeolite powder is (8-12):(1-3):(2-4).

[0015] Preferably, the specific surface area of ​​the ultrafine fly ash is ≥600m² / kg, and the specific surface area of ​​the silica fume is ≥15000m² / kg.

[0016] Preferably, the water-reducing agent is selected from at least one of slump-retaining polycarboxylate water-reducing agents, slow-release polycarboxylate water-reducing agents, and aliphatic water-reducing agents.

[0017] Preferably, the viscosity modifier is selected from at least one of cellulose ether, styrax, and biopolymer adhesive.

[0018] Preferably, the cement concrete further includes limestone powder.

[0019] The present invention also provides a method for preparing the above-mentioned high crack resistance and low heat of hydration cement concrete for crack-sensitive engineering applications, comprising the following steps:

[0020] S1. Preparation of composite admixture premixed slurry: The composite admixture is mixed and stirred with the viscosity modifier and the first part of mixing water to form a uniform slurry A;

[0021] S2. Preparation of water-reducing agent solution: The water-reducing agent is mixed and stirred with the second part of mixing water to prepare solution B;

[0022] S3. Final mixing: The sulfoaluminate cement, the basalt fiber, the third batch of mixing water, the slurry A obtained in step S1 and the solution B obtained in step S2 are put into the mixer for the third mixing and stirring. The mixture is stirred evenly to obtain the cement concrete.

[0023] Preferably, the first portion of mixing water accounts for 30%-50% of the total water content of the cement concrete;

[0024] The second part of the mixing water accounts for 10%-20% of the total water used in the cement concrete;

[0025] The third part of the mixing water accounts for 30%-60% of the total water used in the cement concrete.

[0026] Preferably, limestone powder is also added in step S3, and the amount of limestone powder added is 2%-7% of the mass of sulfoaluminate cement.

[0027] Preferably, the limestone powder is added at the following time: after the sulfoaluminate cement and the basalt fiber are added, during the third mixing and stirring process.

[0028] The technical effects and advantages of this invention are as follows: By combining sulfoaluminate cement with ultrafine composite admixtures in a specific ratio and employing a three-step premixing process, various properties of concrete are coordinated as a whole. The significant microcrystalline nucleation effect of limestone powder at low dosage effectively promotes early hydration and specifically enhances the early strength of concrete; simultaneously, its micro-aggregate filling effect further optimizes the slurry structure, enhancing density and volume stability. The synergistic effect of these two factors achieves precise control over the hydration process and microstructure. This solution not only utilizes the advantages of sulfoaluminate cement and ultrafine composite admixtures to effectively control hydration heat release, but more importantly, its unique three-step premixing process solves the practical mixing problems of uneven dispersion and poor workability of such ultrafine powders and fibers at low water-cement ratios, thus ensuring the density and early strength development of the concrete structure. The resulting concrete, while meeting the requirements of extremely low heat of hydration in crack-sensitive engineering, still exhibits good early crack resistance and workability, achieving simultaneous optimization of multiple key properties. Attached Figure Description

[0029] Figure 1 A process flow diagram for preparing the cement concrete of the present invention. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] Example

[0032] Example 1

[0033] This embodiment provides a crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration.

[0034] 1. Raw material ratio and parameters

[0035] Sulfoaluminate cement: 300 parts

[0036] Composite admixture: 120 parts

[0037] The composite admixture is composed of the following components:

[0038] Ultrafine fly ash: 80 parts, specific surface area ≥600m² / kg

[0039] Silica fume: 16 parts, specific surface area ≥15000m² / kg

[0040] Zeolite powder: 24 parts

[0041] The weight ratio of the three is 10:2:3;

[0042] Basalt fiber: 2.5 parts;

[0043] Slump-retaining polycarboxylate superplasticizer: 5.5 parts;

[0044] Viscosity modifier cellulose ether: 0.3 parts;

[0045] Limestone powder: 6 parts, accounting for 2% of the mass of sulfoaluminate cement;

[0046] Water: 150 portions;

[0047] Water-to-glue ratio: 150 / (300+120+6)≈0.352.

[0048] 2. Preparation method

[0049] The preparation method is a three-step process, and the specific steps are as follows:

[0050] S1. Preparation of composite admixture premixed slurry: All composite admixtures (i.e., ultrafine fly ash, silica fume and zeolite powder), viscosity modifier cellulose ether, and 60 parts of the first mixing water (accounting for 40% of the total water) are put into a high-speed mixer and stirred at 800 r / min for 3 min to prepare a uniform slurry A.

[0051] S2. Preparation of water-reducing agent solution: Stir 22.5 parts of the slump-resistant polycarboxylate water-reducing agent and 22.5 parts of the mixing water in the second part (accounting for 15% of the total water volume) in a container until completely dissolved to prepare solution B.

[0052] S3. Final Mixing: Add sulfoaluminate cement, basalt fiber, and 67.5 parts of the mixing water (45% of the total water content) to a forced mixer and dry mix for 30 seconds. Then, uniformly add limestone powder during the mixing process and continue mixing for 30 seconds. Next, add the slurry A obtained in step S1 and the solution B obtained in step S2 in sequence, and stir at 120 r / min for 4 minutes until the mixture is uniform and the fiber is well dispersed, thus obtaining the cement concrete.

[0053] Example 2

[0054] This embodiment provides a crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration.

[0055] The difference between the above embodiments and Embodiment 1 is that the amount of limestone powder added is different, as shown below.

[0056] In Example 2, the amount of limestone powder added was 21 parts, accounting for 7% of the mass of sulfoaluminate cement. At this time, the water-cement ratio was: 150 / (300+120+21)≈0.340.

[0057] The proportions, parameters, and preparation steps of other raw materials in the above embodiments are the same as those in Example 1.

[0058] Example 3

[0059] This embodiment provides a crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration.

[0060] The difference between the above embodiment and Embodiment 1 is that limestone powder is not added, as detailed below.

[0061] In Example 3: In step S3, limestone is not added during mixing. Instead, sulfoaluminate cement, basalt fiber, and the mixing water from the third part are mixed, and then the slurry A obtained in step S1 and the solution B obtained in step S2 are added sequentially and mixed to obtain the cement concrete. At this time, the water-cement ratio is: 150 / (300+120)≈0.357.

[0062] The proportions, parameters, and preparation steps of other raw materials in the above embodiments are the same as those in Example 1.

[0063] Comparative Example

[0064] Comparative Example 1

[0065] This comparative example provides a crack-sensitive cement concrete for engineering applications with high crack resistance and low heat of hydration.

[0066] 1. Raw material ratio and parameters

[0067] Sulfoaluminate cement: 300 parts

[0068] Composite admixture: 120 parts

[0069] The composite admixture is composed of the following components:

[0070] Ultrafine fly ash: 80 parts, specific surface area ≥600m² / kg

[0071] Silica fume: 16 parts, specific surface area ≥15000m² / kg

[0072] Zeolite powder: 24 parts

[0073] The weight ratio of the three is 10:2:3;

[0074] Basalt fiber: 2.5 parts;

[0075] Slump-retaining polycarboxylate superplasticizer: 5.5 parts;

[0076] Viscosity modifier cellulose ether: 0.3 parts;

[0077] Water: 150 portions;

[0078] Water-to-glue ratio: 150 / (300+120)≈0.357.

[0079] 2. Preparation method

[0080] The preparation process uses a conventional one-time feeding method, and the specific steps are as follows:

[0081] All raw materials, namely sulfoaluminate cement, composite admixtures (ultrafine fly ash, silica fume and zeolite powder), basalt fiber, slump-retaining polycarboxylate superplasticizer, viscosity modifier cellulose ether, and all water, are put into a forced mixer and mixed at 120 r / min for 5-6 minutes until the mixture is homogeneous, thus obtaining the cement concrete.

[0082] Comparative Example 2

[0083] This comparative example provides a crack-sensitive cement concrete for engineering applications with high crack resistance and low heat of hydration.

[0084] The differences between the above comparative examples and Example 1 are as follows.

[0085] In Comparative Example 2: 6 parts of limestone powder (2% of the mass of sulfoaluminate cement) were added, and the water-cement ratio was 150 / (300+120+6)≈0.352. The mixture was prepared using a conventional one-time feeding process, with the specific steps as follows:

[0086] All raw materials, namely sulfoaluminate cement, composite admixtures (ultrafine fly ash, silica fume and zeolite powder), basalt fiber, slump-retaining polycarboxylate superplasticizer, viscosity modifier cellulose ether, and all water, are put into a forced mixer and mixed at 120 r / min for 5-6 minutes until the mixture is homogeneous, thus obtaining the cement concrete.

[0087] The proportions and parameters of other raw materials in the above comparative examples are the same as those in Example 1.

[0088] Comparative Example 3

[0089] This comparative example provides a crack-sensitive cement concrete for engineering applications with high crack resistance and low heat of hydration.

[0090] The differences between the above comparative examples and Example 1 are as follows.

[0091] In Comparative Example 3: 21 parts of limestone powder (7% of the mass of sulfoaluminate cement) were added, and the water-cement ratio was 150 / (300+120+21)≈0.340. The mixture was prepared using a conventional one-time feeding process, with the specific steps as follows:

[0092] All raw materials, namely sulfoaluminate cement, composite admixtures (ultrafine fly ash, silica fume and zeolite powder), basalt fiber, slump-retaining polycarboxylate superplasticizer, viscosity modifier cellulose ether, and all water, are put into a forced mixer and mixed at 120 r / min for 5-6 minutes until the mixture is homogeneous, thus obtaining the cement concrete.

[0093] The proportions and parameters of other raw materials in the above comparative examples are the same as those in Example 1.

[0094] Comparative Example 4

[0095] This comparative example provides a crack-sensitive cement concrete for engineering applications with high crack resistance and low heat of hydration.

[0096] The differences between the above comparative examples and Example 1 are as follows.

[0097] In Comparative Example 4, 6 parts of quartz powder (accounting for 2% of the mass of sulfoaluminate cement) were used to replace the limestone powder in Example 1, and the water-cement ratio was: 150 / (300+120+6)≈0.352.

[0098] The proportions, parameters, and preparation steps of other raw materials in the above comparative examples are the same as those in Example 1.

[0099] It should be noted that the water-cement ratio in both the embodiments and the comparative examples of this invention is controlled within the range of 0.34-0.39. This range is a commonly used technical indicator for crack-sensitive engineering concrete to meet common requirements such as high strength and low permeability. This experiment aims to clearly reveal, through comparison of controlled variables, that while conventional materials and processes (comparative examples) can achieve the same low water-cement ratio, they lead to a chain of problems such as deteriorated workability, insufficient early strength, and poor crack resistance. The specific cementitious system and three-step process provided by this invention are precisely a solution that achieves synergistic optimization of multiple properties such as low heat, early strength, and high crack resistance under these stringent conditions.

[0100] Performance testing and results

[0101] 1. Detection Method

[0102] The performance of the cement concrete and hardened bodies prepared using the above embodiments and comparative examples was tested, and the specific methods are as follows:

[0103] Workability test: The slump and spread of fresh concrete are tested, and its initial and final setting times are determined to evaluate its workability and setting characteristics.

[0104] Mechanical property testing:

[0105] Compressive strength: Prepared and standard-cured cubic specimens, and measured their compressive strength at 1 day, 3 days, 7 days and 28 days.

[0106] Splitting tensile strength: Prepared and standard-cured cubic specimens, and measured their splitting tensile strength at 3 days and 28 days.

[0107] Hydration heat test: The adiabatic temperature rise test method is used to test the adiabatic temperature rise process of concrete and record its maximum temperature rise value (ΔTmax).

[0108] Crack resistance test: The early crack resistance test was conducted using the plate method. Plate specimens were cast and observed under specified conditions. The initial cracking time and the total cracking area within 24 hours were recorded.

[0109] 2. Test Results

[0110] The key performance test results of cement concrete obtained from each embodiment and comparative example are shown in Tables 1 and 2 below.

[0111] Table 1. Test results of workability, compressive strength, and setting properties of the examples and comparative examples.

[0112]

[0113] Table 2. Test results of splitting tensile strength, heat of hydration, and crack resistance of the examples and comparative examples.

[0114]

[0115] Based on Tables 1 and 2, comparing the test results of Examples 1-3 and Comparative Examples 1-3, it can be seen that the workability of the fresh concrete in the comparative examples using the conventional one-time feeding process is significantly deteriorated. The slump and spread are generally more than 30 mm lower than in the examples, and the setting time is extended by more than 1.3 hours. Simultaneously, its early mechanical properties develop slowly; the 1-day compressive strength is more than 4 MPa lower than in the examples, the 3-day splitting tensile strength is more than 0.4 MPa lower, the heat of hydration is poorly controlled, the adiabatic temperature rise is generally more than 2°C higher, and the early crack resistance is poor, with the initial cracking time occurring approximately 1.5 hours earlier, and the cracked area increasing by more than 70 mm² / m² within 24 hours. In contrast, the embodiments of this invention, by using a cementitious system composed of sulfoaluminate cement, specific ultrafine composite admixtures, and limestone powder, combined with a three-step premixing preparation process, enable the concrete to maintain good workability and normal setting speed while synergistically achieving low heat of hydration, high early strength, and high crack resistance, fully meeting the core requirements of crack-sensitive engineering.

[0116] By comparing the test results of Examples 1, 2, and 3, it can be seen that the incorporation of limestone powder has a clear regulatory effect on the performance of this system. Example 1, with 2% limestone powder by mass of cement, achieved 1-day and 3-day compressive strengths of 24.8 MPa and 38.7 MPa, respectively, an increase of approximately 10% compared to Example 3 without limestone powder. Simultaneously, the adiabatic temperature rise was only 38.2℃, and crack resistance was also improved. When the dosage increased to 7%, Example 2 showed further improvements in early strength and density, with a 28-day compressive strength of 64.1 MPa. However, with an adiabatic temperature rise of 39.0℃, its crack resistance was the best, with a crack area of ​​only 108 mm² / m². This indicates that by controlling the limestone powder dosage within the range of 2% to 7%, this invention can specifically regulate the early strength development, heat of hydration release, volume stability, and crack resistance of concrete.

[0117] By comparing the test results of Example 1 and Comparative Example 2, and Example 2 and Comparative Example 3, it can be seen that, with the same composition of cementitious materials, the preparation process becomes the key factor affecting performance. The examples using the three-step process of this invention exhibit significantly better overall performance than the comparative examples using a single-stage feeding method. For example, when both examples contain 2% limestone powder, the 1-day compressive strength of Example 1 is 24.8 MPa, which is 21.6% higher than the 20.4 MPa of Comparative Example 2; its 24-hour crack area is only 118 mm² / m², far lower than the 198 mm² / m² of Comparative Example 2. This demonstrates that the three-step premixing process of this invention plays an indispensable role in achieving uniform dispersion of ultrafine materials and fibers, and ensuring the homogeneity and density of the system's microstructure.

[0118] By comparing the test results of Example 1 and Comparative Example 4, it can be seen that after replacing limestone powder with 2% quartz powder in equal amounts, the 1-day compressive strength of Comparative Example 4 is 20.5 MPa, which is lower than 24.8 MPa of Example 1; its 24-hour crack area is 187 mm² / m², which is also significantly higher than 118 mm² / m² of Example 1. This result verifies that within the system of the present invention, the microcrystalline nucleation effect exerted by limestone powder is specific for improving the early strength and crack resistance of concrete, and its effect cannot be replaced by inert physical filler materials.

[0119] In summary, this invention abandons the traditional approach of relying solely on large amounts of mineral admixtures to reduce the heat of hydration. Through an innovative combination of sulfoaluminate cement, specific ultrafine composite admixtures, and limestone powder, coupled with a three-step premixing process, it effectively controls temperature rise while promoting early hydration, thereby overcoming the defects of slow early strength development and prolonged setting time, and improving volume stability. Therefore, this invention provides a cement concrete that meets the stringent requirements of crack-sensitive engineering projects for rapid construction, high early strength, and high crack resistance.

[0120] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A type of crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration, characterized in that, Based on parts by weight, it includes the following components: 280-350 parts of sulfoaluminate cement; 90-150 parts of composite admixture, wherein the composite admixture comprises ultrafine fly ash, silica fume and zeolite powder; Basalt fiber 0.8-4.5 parts; Water-reducing agent: 4.5-7.0 parts; Viscosity modifier 0.1-0.4 parts; 130-160 parts water; The water-cement ratio of the cement concrete is 0.34-0.

39.

2. The cement concrete according to claim 1, characterized in that, In the composite admixture, the weight ratio of ultrafine fly ash, silica fume and zeolite powder is (8-12):(1-3):(2-4).

3. The cement concrete according to claim 1, characterized in that, The specific surface area of ​​the ultrafine fly ash is ≥600m² / kg, and the specific surface area of ​​the silica fume is ≥15000m² / kg.

4. The cement concrete according to claim 1, characterized in that, The water-reducing agent is selected from at least one of slump-retaining polycarboxylate water-reducing agents, slow-release polycarboxylate water-reducing agents, and aliphatic water-reducing agents.

5. The cement concrete according to claim 1, characterized in that, The viscosity modifier is selected from at least one of cellulose ether, gluten gum, and biopolymer gum.

6. The cement concrete according to claim 1, characterized in that, The cement concrete also includes limestone powder.

7. A method for preparing crack-sensitive engineering cement concrete with high crack resistance and low heat of hydration according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of composite admixture premixed slurry: The composite admixture is mixed and stirred with the viscosity modifier and the first part of mixing water to form a uniform slurry A; S2. Preparation of water-reducing agent solution: The water-reducing agent is mixed and stirred with the second part of mixing water to prepare solution B; S3. Final mixing: The sulfoaluminate cement, the basalt fiber, the third batch of mixing water, the slurry A obtained in step S1 and the solution B obtained in step S2 are put into the mixer for the third mixing and stirring. The mixture is stirred evenly to obtain the cement concrete.

8. The method according to claim 7, characterized in that, The first portion of mixing water accounts for 30%-50% of the total water used in the cement concrete; The second part of the mixing water accounts for 10%-20% of the total water used in the cement concrete; The third part of the mixing water accounts for 30%-60% of the total water used in the cement concrete.

9. The method according to claim 7, characterized in that, In step S3, limestone powder is also added, and the amount of limestone powder added is 2%-7% of the mass of sulfoaluminate cement.

10. The method according to claim 9, characterized in that, The limestone powder is added at the following time: after the sulfoaluminate cement and the basalt fiber are added, it is added during the third mixing process.